Lactate Modulates Cellular Metabolism Through Histone Lactylation-Mediated Gene Expression in Non-Small Cell Lung Cancer - Jiang, Jun; Huang, DengLiang; Jiang, Yuan; Hou, Jing; Tian, MeiYuan; Li, JianHua; Sun, Li; Zhang, YaoGang; Zhang, Tao; Li, ZhiQin; Li, ZhongCheng; Tong, SiXian; et al. (Frontiers in Oncology, 2021)
Lactate has been observed to fuel the TCA cycle and is associated with the progression of human lung cancer, the leading cause of cancer deaths worldwide. However, the effect of lactate on lung cancer metabolism is rarely reported. In this study, disordered metabolism in non-small cell lung cancer was demonstrated by increased G6PD and SDHA protein levels via immunofluorescence, and up-regulated lactate dehydrogenase was found to be associated with poor prognosis. Flow cytometry and a Seahorse XFe Analyzer were utilized to detect the effect of lactate on glycolysis and mitochondrial function in non-small cell lung cancer cells. The results showed that in non-small cell lung cancer cells lactate attenuates glucose uptake and glycolysis while maintaining mitochondrial homeostasis, as indicated by improved mitochondrial membrane potential. Further exploration found that mRNA levels of glycolytic enzymes (HK-1, PKM) and TCA cycle enzymes (SDHA, IDH3G) were respectively down-regulated and up-regulated by lactate, and increased histone lactylation was observed in promoters of HK-1 and IDH3G via chromatin immunoprecipitation assay. Taken together, the results indicate that lactate modulates cellular metabolism at least in part through histone lactylation-mediated gene expression in non-small cell lung cancer.